Productive and reproductive performance of local and cross-breed dairy cattle in Kanchan rural municipality, Rupandehi, Nepal - SHARMA, SAILAJA; GAUTAM, MANISH; DHAKAL, AVISH; SAPKOTA, SWASTIKA; SHAH, SHAMBHU (The Indian Journal of Animal Sciences, 2025)
A household survey was conducted to compare the productive and reproductive performance of local and crossbreed dairy cattle under farmer’s management conditions in Kanchan Rural Municipality, Rupandehi, Nepal. A total of 115 households were surveyed, and the data of 141 cattle, local (n=38), Jersey cross (n=64), and Holstein Friesian (HF) cross (n=39), were collected and analyzed to determine their productive and reproductive performance. Peak milk yield per day and average milk yield per day were significantly lower in local than Jersey cross and HF cross, respectively. Lactation length was shorter and dry period was longer in local than Jersey cross and HF cross. Age at first mating, age at first calving, and postpartum heat period were significantly longer in local than Jersey cross and HF cross. However, calving to conception interval, calving interval, and service per conception were shorter in Local than JC and HF Cross. In the study, 31% had a history of repeat breeding, 5.7% had a history of abortion, and 24% of cattle had a history of anestrus. The incidence of repeat breeding was significantly higher in HF cross (59%), followed by Jersey cross (25%), and lower in local (13.2%). So, in conclusion, despite the overall productive and reproductive performance being higher, exotic cattle lack some traits that are more efficiently preserved in local cattle. The study also suggests using local cattle in a crossbreeding program to increase disease resistance and more efficient production.